2020
DOI: 10.1016/j.aca.2019.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Precision biomarker discovery powered by microscopy image fusion-assisted high spatial resolution ambient ionization mass spectrometry imaging

Abstract: Mass spectrometry imaging (MSI) using ambient ionization technique enables a direct chemical investigation of biological samples with minimal sample pretreatment. However, detailed morphological information of the sample is often lost due to its limited spatial resolution. In this study, predictive high-resolution molecular imaging was produced by the fusion of ambient ionization MSI with optical microscopy of routine hematoxylin and eosin (H&E) staining produces. Specifically, desorption electrospray ionizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…A high voltage was applied to the syringe needle, and solvent was continuously perfused, such that a liquid microjunction formed between the capillaries at the sample surface. Desorbed lipids were then aspirated through the second capillary toward the mass spectrometer inlet, where electrospray ionization and subsequent detection occurred (30)(31)(32). NanoDESI-MS was performed in a negative ion mode at m/z 200-1,200, with methanol:acetonitrile:ethyl acetate 50:35:15 (vol/ vol/vol) as the solvent at 2.5 µL/min flow rate.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…A high voltage was applied to the syringe needle, and solvent was continuously perfused, such that a liquid microjunction formed between the capillaries at the sample surface. Desorbed lipids were then aspirated through the second capillary toward the mass spectrometer inlet, where electrospray ionization and subsequent detection occurred (30)(31)(32). NanoDESI-MS was performed in a negative ion mode at m/z 200-1,200, with methanol:acetonitrile:ethyl acetate 50:35:15 (vol/ vol/vol) as the solvent at 2.5 µL/min flow rate.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…Interestingly, the study showed that the lipid distribution in different areas of the tissue was similar, independent of the species, suggesting lipid profiles are conserved across different species. Lin et al applied DESI and nanoDESI imaging combined with MALDI‐MSI and optical microscopy for the analysis of lipids and proteins in murine brain and kidney tissues and cancerous human tissues 118 . With a spatial resolution of 5 μm and 100 μm for DESI/nanoDESI and MALDI, respectively, the multimodal tissue imaging approach enabled improved precision in the determination of tumor margins, along with the detection of several new potential tumor biomarkers.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…However, the technique has not been extensively used for MSI analysis of hair, probably because of its relatively low spatial resolution. Recent advances have led to improved resolutions of between 20 and 100 µm [70,71], but the average diameter of adult human hair varies between 45 and 110 µm [18]. As the technique evolves towards improved resolution [70], it may find application in future hair analyses.…”
Section: Analysis Of Hair By Mass Spectrometry Imagingmentioning
confidence: 99%
“…Recent advances have led to improved resolutions of between 20 and 100 µm [70,71], but the average diameter of adult human hair varies between 45 and 110 µm [18]. As the technique evolves towards improved resolution [70], it may find application in future hair analyses.…”
Section: Analysis Of Hair By Mass Spectrometry Imagingmentioning
confidence: 99%